PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN HOTEL NAGOYA PLASA KOTA BATAM - Kurnia, Okki; Sukma Prihatini (Puslitabmas Batam Tourism Polytecnic, 2022)
Hotel Nagoya Plasa is one of the oldest hotel in Batam City, until 2020 the hotel will turn 28 years old. The existence of the hotel has been long and the turnover phenomenon is not really significant and it is found that many employees with permanent contracts have worked for a long time at this hotel so that indirectly many organizational cultures grow independently among employees. This study aims to determine the effect of organizational culture on employee performance at Hotel Nagoya Plasa. Organizational culture variables were tested using 6 dimensions. Employee performance variables were tested using 7 dimensions. This research was conducted at the Nagoya Hotel Plasa. The research method used is quantitative research methods, data collection techniques are done by distributing questionnaires. The sample used is a saturated sample of 78 samples, which are all employees. Data analysis used descriptive analysis and simple linear regression analysis using SPSS 26. The results of this study are that organizational culture has a significant effect on employee performance at Hotel Nagoya Plasa.